Etymological Experiments and Corrections - ZAKARYAN, HOVHANNES (Bulletin of Yerevan University B: Philology, 2021)
The present article, proceeding from morpho-semantic analyses and analyses of linguistic universals, offers to derive a number of Armenian words, still not etymologized or considered to be borrowings, from PIE root *smē- (*smeī-, *sm-ei-) "to smear, rub" and its derivative variants (extended by root determinatives and framed by different ablaut steps). They are: մերսել "massage" [
Keywords: the Armenian language, etymology, Protoindoeuropean, root, derivative, determinative, vowel gradation, root variants